Bending behavior of splice connection for corner-supported steel modular buildings. (1st January 2022) - Lyu, Yi-Fan; Li, Guo-Qiang; Cao, Ke; Zhai, Si-Yuan; Wang, Yan-Bo; Mao, Lei; Ran, Ming-ming
Highlights: Four bending tests for splice connection are tested and simulated. Bilinear two-stage bending behavior for connection is discovered. Classification of the proposed splice connection is analyzed. A comprehensive parametric study is conducted. Satisfactory tolerance for lost of bolt-pretension force is found. Abstract: Splice connection consisting of slip-critical high strength bolt and side plate is a promising connection type for future modular construction. However, recognitions on basic performance for this connection are still limited. To fill this gap, this paper conducted a comprehensive research on basic bending behavior of a simple splice connection proposed by the authors for corner-supported steel modular building. The basic bending behavior of the proposed splice connection was analyzed in details by combined experiments and numerical simulations. It is found that the proposed splice connection can achieve a favorable ductile behavior in bending. Bilinear profile with two stages is clearly observed in the relationship between moment and connection rotation. These two stages have different stiffness but the applied load can keep increasing in the second stage with excessive deformation of the specimen. Such phenomenon reveals adequate reserve of bending resistance for the proposed splice connection under large deformation scenario. Based on method of farthest point, a transition point is defined and determined in the relationship between moment and connection rotation. This transition point represents an important change in the bending behavior, which is valuable for practical design. Numerical simulations are also introduced to supplement the tests. The analyses on stress states of components and variation in bolt pre-tension force properly explains anisotropy in resistance at the transition point for different loading directions. A parametric study is further conducted. Results indicate that the proposed splice connection possesses satisfactory tolerance for loss of bolt pre-tension force in the practical construction.